L’AEROFOTOTECA NAZIONALE RACCONTA.... Le foto aeree per la mappatura di ordigni bellici inesplosi in contesti archeologici - Noto, Miriam (GEOmedia, 2020)
Example of a Geographic Information System for the mapping through historical aerial photos of archaeological sites bombed during the Second World War and for assessing the risk of unexploded bombs in the subsoil.